BELAJAR DARI PERILAKU (Sebuah resensi terhadap buku berjudul: Learning from behavior: how to understand and help ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œchallengingÃƒÂ¢Ã¢â€šÂ¬Ã‚Â children in school written by: James E. Levine) - Zidniyati Zidniyati (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2016)
This writing is a review of a book entitled ÃƒÂ¢Ã¢â€šÂ¬Ã‹Å“Learningfrom behavior: how to understand and help ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œchallengingÃƒÂ¢Ã¢â€šÂ¬Ã‚Âchildren in school. In the book written by James E. Levinewhich was published in 2007 by Praeger Publisher, Westport,London, explained about the connection betweenunderstanding behavior of ÃƒÂ¢Ã¢â€šÂ¬Ã‹Å“challengingÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ children in school anddeveloping creative interventions for changing it. This book isbased on an accumulation of many years of clinical practise,observation, thinking, and discourse. It is intended to add tothe ongoing anaklogue about what will help children amid thecombined challenges of developmental, family, and culturalchange. The hope is that as it core, this book which is writtenin 118 pages, will add another voice that augments James E.LevineÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s repertoire of best practices and, at the same time,offers a new way to frame the discussion on childÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s needs,one that is based on the recognized importance of meaningfulrelationships and an enhanced understanding of childhoodbehavior. It is intended for a wide range of clinicalpractitioners, especially those who work in school settings aswell as guidance staff, special educators, regular educationteachers, alternatives classroom staff, school administrators,graduate students in the mental health disciplines, andnotably, parents who are invested in reflecting on the kinds ofbehavioral and preventive strategies that can thoughtfully beemployed in the service of childrenÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s needs everywhere,included in Indonesia. In addition, Indonesia as a developingcountry has lots in common cases with some countries fromwhich Levine took as examples of other developing countrieswith their ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œchallengingÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ childrenÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s setting. The deepunderstanding of this book will offer lots of advantageouscontribution to people concerning in ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œchallengingÃƒÂ¢Ã¢â€šÂ¬Ã‚Â childrenand to policy makers in Indonesia as one of developingcountry which has been running on to its inclusive educationalsystem amid the various problem to be solved.